2017
DOI: 10.3889/oamjms.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Proteins and Microsatellite Instability in Colorectal Carcinoma (MLH1, MSH2, MSH6 and PMS2): Histopathological and Immunohistochemical Study

Abstract: BACKGROUND:Colorectal cancer (CRC) is one of the most common cancers worldwide. Microsatellite instability (MSI) is detected in about 15% of all colorectal cancers. CRC with MSI has particular characteristics such as improved survival rates and better prognosis. They also have a distinct sensitivity to the action of chemotherapy.AIM:The aim of the study was to detect microsatellite instability in a cohort of colorectal cancer Egyptian patients using the immunohistochemical expression of mismatch repair protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…However, they found in patients with metastatic disease, KRAS mutations were more common in individuals older than 65 years (p = 0.035) [16]. Regarding MSI status, 57.9% of our patients had MSI-H CRC which was reported as a factor associated with improved prognosis [17]. Previous studies found that MSI-H sporadic CRCs are the most often (about 70-95%) caused by alteration of the MLH1 gene via somatic promoter hypermethylation [18].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, they found in patients with metastatic disease, KRAS mutations were more common in individuals older than 65 years (p = 0.035) [16]. Regarding MSI status, 57.9% of our patients had MSI-H CRC which was reported as a factor associated with improved prognosis [17]. Previous studies found that MSI-H sporadic CRCs are the most often (about 70-95%) caused by alteration of the MLH1 gene via somatic promoter hypermethylation [18].…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies found that MSI-H sporadic CRCs are the most often (about 70-95%) caused by alteration of the MLH1 gene via somatic promoter hypermethylation [18]. In other Egyptian studies, MSI-H was found in 37% and 30.8% of their patients [17,19]. This difference may be attributed due to different detective methods to some extent.…”
Section: Discussionmentioning
confidence: 88%
“…The RAS gene is a predictive biomarker for the resistance to anti-EGFR monoclonal antibody (MoAb) treatment in mCRCs ( Amado et al, 2008 ; Punt, Koopman & Vermeulen, 2016 ). However, geographic and racial differences between Chinese and other countries were reported ( Huang et al, 2010 ; Ismael et al, 2017 ; Kim et al, 2007 ; Vasovcak et al, 2011 ; Ye et al, 2015 ), which need to be validated with large sample amounts. Furthermore, data regarding RAS mutation frequency and dMMR CRC is not consistent in China.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between dMMR status and clinicopathological characteristics were controversial ( Ismael et al, 2017 ; Jin et al, 2008 ; Ribic et al, 2003 ; Sinicrope et al, 2011 ). Reports from three independent Chinese groups ( Huang et al, 2010 ; Jin et al, 2008 ; Ye et al, 2015 ) indicated that dMMR had specific associations such as female gender, right sided colon tumors and mucious tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations cause de ciencies in DNA repair, resulting in a high frequency of replication errors. Genetic analysis and detection of protein expression by immunohistochemistry (IHC) are important in diagnosing LS [5,6]. MTS is primarily related to mutations in MSH2 and is characterized by skin tumors (such as sebaceous adenomas, skin squamous cell carcinomas) [9].…”
Section: Introductionmentioning
confidence: 99%